The Association between ACTN3 R577X Polymorphism and Range of Motion: A Systematic Review and Meta-analysis - Saito, Mika; Zempo, Hirofumi; de Almeida, Kathleen Yasmin; Homma, Hiroki; Kikuchi, Naoki (International Journal of Sports Medicine, 2023)
The R577X polymorphism in the α-actinin-3 gene (ACTN3) is associated with muscle strength and power; there is an association between ACTN3 R577X polymorphism and range of motion (ROM). We examined the effect of the ACTN3 R577X polymorphism on ROM through meta-analysis and systematic review. Relevant studies published before April 14, 2022 were identified from the PubMed database using the following keywords and Boolean operators: (“flexibility” or “Joint Range of Motion” or “Joint Flexibility” or “Range of motion”) and (“ACTN3” or “alpha-actinin 3”). Studies that met the following criteria were included: (1) published in English, (2) included human subjects, (3) provided ROM measurements, and (4) analyzed the ACTN3 R577X genotype. A total of 2908 participants from seven studies were included in the meta-analysis. The additive genetic model was assessed using a meta-regression model, and dominant and recessive models were analyzed using a random effects model. The ROM in the XX+RX genotype was significantly higher than that in the RR genotype (recessive model: p<0.001), and it increased additively in the order XX>RX>RR (additive model: p=0.029). However, no significant association was observed in the dominant model. These findings further elucidate the association between flexibility and the ACTN3 R577X genotype.
Keywords: ACTN3; α-actinin-3; genotype; flexibility; ROM